Self-Efficacy of nurses in COVID-19 isolation room of Sanglah Hospital, Denpasar: A mixed-method study - Pande, Rai Dewi Damayanthi; Lubis, Dinar Saurmauli; Lesmana, Cokorda Bagus Jaya (Universitas Udayana, 2022)
Background and purpose: Nurses' self-efficacy during the pandemic is different from their self-efficacy before the pandemic. Managing self-efficacy is one way to support nurses' mental well-being and resilience. This study aims to describe and determine factors related to nurses' self-efficacy in the COVID-19 Isolation Room of Sanglah Hospital, Denpasar, Bali Province. Methods: This is a mixed-methods study with a sequential explanatory design. In the first stage, a cross-sectional survey was conducted with a questionnaire in 132 nurses selected with total sampling. Statistical analysis was carried out using Chi-Square Test and Fisher's Exact Test at a 95% confidence level, to identify a relationship between nurses’ characteristics and sources of self-efficacy with their self-efficacy levels. Subsequently, qualitative in-depth interviews were conducted with 12 informants selected by purposive sampling. Qualitative data were analyzed using thematic analysis. Results: In the quantitative study, it was found that there was no relationship between the characteristics of nurses (age, gender, education level, years of service and training) and the level of self-efficacy (p>0.05). Meanwhile, the sources of efficacy (mastery experience, vicarious experience, social persuasion, physiological and emotional conditions) were found significantly associated with the level of self-efficacy (p<0.05). The qualitative study found that matters in line with these results, and other variables related to self-efficacy were personal, organizational, and external variables. Conclusion: Sources of self-efficacy that nurses can utilize, as well as opportunities and support provided by nurse leaders, developed self-efficacy in treating COVID-19 patients. It is necessary to increase the significance of sources of self-efficacy, personal variables, and organizational support to increase self-efficacy.